A Semantic Study : Figurative Language Used In Payuh Teduh Songs Lyrics - Muhammad Natsir; Bahagia Saragih; Rafika Dewi Nasution (Britain International for Academic Research (BIAR) Publisher, 2022)
This research aims to analyze the style of figurative language and reason used in the song lyric of Payung Teduh. This research is expected the result of this study will be useful for the reader especially in knowing what kinds of figurative language are and reasont of contextual meanings of figurative language used in the song lyric by Payung Teduh. In this research use descriptive qualitative method that the data of songs are Payung Teduh Album got from kapanlagi.com. The result found that there are some kinds of figurative language used in Payung teduh song entitle angin pujaan hujan, kucari kamu, diujung malam, tidurlah, berdua saja, resah and Akad that limited to simile, metaphor, personification and irony. The contextual which means of each figurative language is also noted clearly.